2010
DOI: 10.2169/internalmedicine.49.2633
|View full text |Cite
|
Sign up to set email alerts
|

Localized Amyloidosis at the Site of Repeated Insulin Injection in a Diabetic Patient

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
112
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(114 citation statements)
references
References 9 publications
1
112
0
1
Order By: Relevance
“…However, another ligand of RAGE is the amylin polypeptide, which is co-produced with insulin by the pancreatic beta cells in response to elevation of plasma glucose [46]. Moreover, there is speculation that insulin may also bind to RAGE, since there is evidence of amyloidosis composed of iatrogenic A-Ins type amyloid [47]. Indeed, other investigators have suggested that proinflammatory RAGE and HLA II DRB1 polymorphisms may synergise to activate the immune response in diabetes complications [48].…”
Section: Discussionmentioning
confidence: 99%
“…However, another ligand of RAGE is the amylin polypeptide, which is co-produced with insulin by the pancreatic beta cells in response to elevation of plasma glucose [46]. Moreover, there is speculation that insulin may also bind to RAGE, since there is evidence of amyloidosis composed of iatrogenic A-Ins type amyloid [47]. Indeed, other investigators have suggested that proinflammatory RAGE and HLA II DRB1 polymorphisms may synergise to activate the immune response in diabetes complications [48].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with AIns may present to the clinician as a direct result of noticing the nodular deposits or symptoms thereof. They may also have associated brittle diabetes as a result of unpredictable release of insulin from these nodules [16,17]. Additionally, inhaled insulin has also been shown to result in amyloid fibril formation in mice lungs with resultant pulmonary toxicity [18].…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenic deposition of insulin aggregate at the injection site is a notorious complication for the intravenous insulin injection and subcutaneous infusion (Dische et al 1988;Shikama et al 2009). Accordingly, insights into this deposition process can provide useful information, showing propensity of different insulin variants for the pathogenic aggregation.…”
Section: Comparing Aggregation Propensity Of Acetylated and Non-acetymentioning
confidence: 99%